Pendekatan Quality Function Deployment (QFD) dalam proses pengembangan desain produk Whiteboard Eraser V2 - Emmy Nurhayati (Productum: Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2022)
The use of a whiteboard eraser is unavoidable in teaching and learning activities. However, in its use, whiteboard erasers are often found that are easily damaged or of poor quality. Some things that can happen are the eraser cloth is torn, the cloth is detached from the place and the marker ink marks on the eraser body. The Quality Function Deployment (QFD) method approach is used to develop product designs in an effort to correct the shortcomings of the whiteboard eraser that has been used previously. The data obtained were obtained from questionnaires distributed to respondents by considering the statement attributes to determine the user's wishes. The results obtained from the overall planning matrix can be identified with the needs of the eraser user, namely the Interest Level with the highest value of 4.36, namely A12 (comfortable product to use), the highest Satisfaction Level of 4.07, namely A10 (Easy to absorb eraser fabric), Improvement Ratio with a value of The highest score is 1.35, namely A9 (the eraser body is made of lightweight and strong material) and Normalized Raw Weight with the highest value of 13%, namely A11 (the cloth material is not easily torn). The design of the V2 whiteboard eraser was designed in an effort to meet user needs with the QFD concept according to Indonesian anthropometric data and to obtain a product design in the form of a V2 whiteboard eraser which has a blue color with the addition of batik motifs and accessories, a body made of Dutch teak wood, type the fabric used is cotton, and the fabric/filling can be changed.